ALIH MEDIA DIGITAL DALAM KEGIATAN PELESTARIAN INFORMASI - Fatmawati, Endang (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
The purpose of this article is to explain the activities of information preservation, digital media transfer, and digital reproduction transformation. Preservation of library material information is different from physical preservation of library materials. This article is more about preserving the information. Digitization is one of the efforts to preserve information on library materials. Media transfer of library materials is included in the activity of preserving the information content. Transferring media means processing from printed form to digital form. Librarians must always improve their competence in carrying out media transfer activities, repackaging information, and preserving information on library materials. The library materials that are transferred to the media are prioritized which are classified as rare or unique. It is necessary to preserve information on library materials to protect the contents of the information so that it is not destroyed, can still be accessed, and to increase access by users. Digital preservation must also be done to preserve digital content information so that it can last a long time. Reproduction of digital library materials is printed in the form of images or photos, written in the form of script sheets, and recorded in the form of film negatives.